2020
DOI: 10.1002/ece3.6777
|View full text |Cite
|
Sign up to set email alerts
|

Sweet tooth: Elephants detect fruit sugar levels based on scent alone

Abstract: The ability to assess food quality is crucial to all organisms. Fleshy fruits are a major source of nutrients to various animals, and unlike most food sources, have evolved to be attractive and to be consumed by animals to promote seed dispersal. It has recently been established that fruit scent—the bouquet of volatile chemicals emitted by ripe fruit—is an evolved communication system between plants and animals. Further, it has been argued that chemicals that are synthesized from sugar and its products may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 46 publications
0
29
0
Order By: Relevance
“…Our data, although limited to three species, suggest that nasal turbinate volume may not be useful for predicting active sniffing in a fruit foraging context, and might be a better metric of other aspects of olfaction, an idea that invites future study. Olfactory perception remains a poorly understood area and is influenced by diverse factors, including the shape of the turbinates and nasal cavity, air flow rate across the olfactory epithelium, olfactory neuron density, OR diversity and their responsiveness to natural odours [ 27 , 32 , 59 , 60 ]. While we examined a narrow ecological context (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Our data, although limited to three species, suggest that nasal turbinate volume may not be useful for predicting active sniffing in a fruit foraging context, and might be a better metric of other aspects of olfaction, an idea that invites future study. Olfactory perception remains a poorly understood area and is influenced by diverse factors, including the shape of the turbinates and nasal cavity, air flow rate across the olfactory epithelium, olfactory neuron density, OR diversity and their responsiveness to natural odours [ 27 , 32 , 59 , 60 ]. While we examined a narrow ecological context (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…the smell of ripe fruit, the odor of predators in the distance) (Nevo et al. 2020 ). Whether an animal is navigating within a patch, between patches, or across entire landscapes (Senft et al.…”
Section: The Olfactory Landscape Builds Upon a Distinct Information C...mentioning
confidence: 99%
“…For example, Peris et al 24 looked at the dietary habits of wild seed disperser and pulp feeding species across two biomes and found that rotting fruits inoculated with Penicillium digitatum fungus were overwhelmingly preferred by local frugivores. Others found that African elephants (Loxodonta africana) could identify fruit sugar content based on scent alone, with volatile ethanol in the scent plume accounting for nearly 50% of the variance in which fruits were preferred 27 . Similarly, two nectar-feeding primates, the slow loris (Nycticebus coucang) and ayeaye (Daubentoniab madagascariensis), were found to prefer 1%-5% v/v ethanol solutions over sucrose-sweetened control solutions in a two-choice test 28 .…”
Section: Frugivores and Alcohol Consumptionmentioning
confidence: 99%